Herpes Simplex Virus Epithelial Keratitis In Vivo Morphology in the Human Cornea - Tabery, Helena M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Herpes Simplex Virus Epithelial Keratitis provides a kind of ‘living histology’, revealing both morphological and dynamic features of the disease, and explaining the mechanisms behind them. It discusses in detail: ° the result of herpes simplex virus impact on the living human epithelium ° the step-by-step dynamics of healing during a successful treatment ° the complications and sequelae of infection The case studies presented demonstrate the application of these observations in clinical practice. This unique guide offers insights helpful in differential diagnostics and the recognition of lesser known variants, as well as complications. It is also useful for the follow–up of treatment results and the differentiation between an active infection and sequelae. It is an invaluable aid for ophthalmologists and researchers working with ocular surfaces.
Preface -- About Epithelial Keratitis -- About Herpes Simplex Virus (HSV) Epithelial Keratitis -- The Morphology of Herpes Simplex Virus Epithelial Keratitis -- HSV Cytopathic Effect - Early Changes -- HSV Cytopathic Effect - Advanced Changes -- Early HSV in Vivo Lesions - Surface Elevation and Disruption -- An Advanced HSV in Vivo Lesion - Loss of Substance -- HSV Lesions - Surface Elevation, Depression, and Fluid Diffusion -- Rose Bengal Dye Staining of HSV Lesions -- A HSV Dendritic Figure (1) -- A HSV Dendritic Figure (2) -- The Origin of HSV Dendritic Figures -- Various Shapes of HSV Dendritic Figures -- Some Other Shapes of HSV Lesions -- Precursors of HSV Geographic Lesions -- HSV Geographic Lesions -- A Case of Primary HSV Keratitis.-Healing of Herpes Simplex Virus Epithelial Keratitis Treated with Acyclovir Ointment, and Short-term Sequelae of the Infection -- Healing of HSV Epithelial Keratitis with Acyclovir Ointment -- Healing of HSV Epithelial Keratitis with Acyclovir Ointment. A treatment failure -- Side Effects of Acyclovir Ointment -- Complications, Accompanying Signs, Recurrences, and Long-term Sequelae of Herpes Simplex.-Virus Epithelial Keratitis -- Case 1. HSV Epithelial Keratitis - a Fresh and an Older Lesion -- Healing Followed by Epithelial Breakdown, and a New Repair (Case 1, cont.) -- Case 2. Healing of HSV Epithelial Keratitis, Accompanying Signs, and Sequelae -- Case 3. HSV Epithelial Keratitis and Stromal Infiltrates -- Case 4. HSV Epithelial Keratitis Preceded by Anterior Uveitis and Disciform Keratitis -- HSV Epithelial Keratitis and Dry Eye (Case 4, cont.) -- Case 5. Recurrent HSV Epithelial Keratitis in a Patient with Dry Eye.-Bibliography -- Index.
Keywords: Ophthalmology; Infectious diseases; Ophthalmology; Infectious Diseases